Predictors of Perceived Barriers to Mammography in Korean Women - Jung-Hee Kim, RN, PhD; Oksoo Kim, RN, PhD (Elsevier, 2008)
The purpose of the study was to investigate the effects of cancer fatalism, breast cancer fear, and health motivation on perceived barriers to mammography in Korean women living in the community. Methods: The sample for this study was a convenience sample of 138 Korean women. Data were collected through a questionnaire that included Cancer Fatalism, the Breast Cancer Fear Scale, Health Motivation, and the Revised Barriers Scale for Mammography. The data were analyzed by multiple regression using SPSS version 11.0. Results: The level of cancer fatalism was low with a mean of 1.07. The levels of fear of breast cancer, health motivation and barriers to mammography were moderate with means of 27.10, 26.44 and 25.80, respectively. Age (F = 3.22, p = .02) was significantly related to mammography barriers but breast-related characteristics were not significantly associated with any mammography barriers. Health motivation (b =−.34, p = .00) and breast cancer fear (b = .22, p = .00) were predictive variables of perceived barriers to mammography. The model explained 19% of the variance in mammography barriers scores (F = 9.98, p = .00). Conclusion: Nurses who work with Korean women for breast cancer screening need to assess these predictive factors, including health motivation and breast cancer fear. Further extensive research will be needed to demonstrate the relationship between breast cancer fatalism and perceived barriers to mammography.